Evaluating drug cost per responder and number needed to treat associated with lixisenatide on top of glargine when compared to rapid-acting insulin intensification regimens on top of glargine, in patients with type 2 diabetes in the UK, Italy, and Spain. (3rd June 2017) - Afonso, Marion; Ryan, Fay; Pitcher, Ashley; Lew, Elisheva
Abstract: Objectives: This study investigated the cost per responder and number needed to treat (NNT) in type 2 diabetes mellitus (T2DM) patients for lixisenatide compared to insulin intensification regimens using composite endpoints in the UK, Italy, and Spain. Methods: Efficacy and safety outcomes were obtained from GetGoal Duo-2, a 26-week phase 3 trial comparing lixisenatide vs insulin glulisine (IG) once daily (QD) and three times daily (TID). Response at week 26 was extrapolated to 52 weeks, assuming a maintained treatment effect, based on long-term evidence in other T2DM populations. Responders were defined using composite end-points, based on an HbA1c threshold and/or no weight gain and/or no hypoglycemia. The HbA1c threshold was varied in sensitivity analyses. Annual treatment costs were estimated in euros (1 GBP = 1.26 EUR), including drug acquisition and resource use costs. Cost per responder was computed by dividing annual treatment costs per patient by the proportion of responders. Results: Lixisenatide was associated with the lowest cost per responder for all composite end-points that included a weight-related component. For the main composite end-point of HbA1c ≤7.5% AND no weight gain AND no symptomatic hypoglycemia, cost per responder results were: UK: 6, 867€, 8, 746€, and 12, 410€; Italy: 7, 057€, 9, 160€, and 12, 844€; Spain: 8, 370€, 11, 365€, and 17, 038€, for lixisenatide, IG QD, and TID, respectively. The NNT analysis showed that, for every 6.85 and 5.86 patients treated with lixisenatide, there was approximately one additional responder compared to IG QD and TID, respectively. Limitations: A limitation of the clinical inputs is the lack of 52-week trial data from GetGoal Duo-2, which led to the assumption of a maintained treatment effect from week 26 to 52. Conclusions: This analysis suggests lixisenatide is an efficient economic resource allocation in the UK, Italy, and Spain.